Carbon nanofibers on plastic substrates : characterization and applications - Sim, Hwa San (2010)
Carbon nanofibers (CNFs) as a promising candidate for field emitters have attracted a lot of attention from the research community, due to its low field emission threshold, high aspect ratio, good chemical stability and excellent mechanical strength. Although many applications involving field emitters on planar substrates have been reported, there are only a few reports on the physics and applications of CNF based emitters grown onto flexible plastic substrates. This thesis aims to address the issues on the fabrication; characterization, reliability and applications of the CNF based field emitters on flexible polyimide film. In addition, this thesis is also devoted to study the characteristics of a single CNF in order to understand the field emission properties at sub 100 nm gap regime, its field emission noise, electrical and physical properties. The results may have significant implication on the design of vacuum nano-devices such as compact high-power frequency devices. The CNF film on plastic substrates was prepared by an ion beam technique. Argon ions were bombarded onto carbon-coated substrates at room temperature, inducing conical protrusions of around 0.2 ~ 0.5 um in length which possessed a long CNF of 0.3 ~ 5 um in length and 10 ~ 30 nm in diameter. The CNFs were also abundant and uniformly distributed. The threshold field of the CNF film is around 3 V/um at a current density of 1 uA/cm^2; with a high field enhancement factor of ~ 3000. The field emission mechanism of a single CNF at sub-100 nm regime has been investigated over a range of anode to CNF tip separations (S) of 20-5500 nm.